Political Transformations and Dominant Symbols in Contemporary Iraq: A study in political anthropology (Journal of the College of Education for Women, 2025)
This research aims to study "political transformations and dominant symbols in Iraq" by clarifying the impact of these transformations on the production or reinforcement of certain symbols at the expense of others. "Hegemony" refers to the influence that these symbols wield and acquire through power over a reinforced social capital. This seeks to answer the central question: What contexts enable a particular symbol to exert influence and dominance in society? The study relied on the (night and day) approach of the anthropologist Gilbert Durand, which is based on a symbolic triad that dominates society, namely: (the warrior, the clergyman or priest, the peasant). The study demonstrates its conformity to Iraq in its political and social transformations from the establishment of the state in 1921 until 2003. The study was based on the method of historical tracking based on recalling a group of incidents accompanying the political transformations and their contexts, and demonstrating their tools and procedures that express the influence of one of the social symbols. The study revealed that the rise of a symbol is reinforced by the authority of the state through laws and procedures that increase its influence in society. Symbolism arises within social and political conditions that enable the state to exert its influence and represent the dominant force in politics and society. The study concludes that political and social transformations must be interpreted in light of dominant elements that represent the power and influence of authority, whether through force (the warrior), containment (the religious figure), or sustenance (the peasant).